Dinamika Kelimpahan Kuntul Kerbau (Bubulcus ibis Linnaeus 1758) Di Tempat Pembuangan Akhir (TPA) Jatibarang, Semarang - Fadila, Muhammad Imam; Mardiastuti, Ani; Mulyani, Yeni Aryati (Bioma : Berkala Ilmiah Biologi, 2025)
The cattle egret (Bubulcus ibis) utilizing landfill sites for foraging is not a new or rare phenomenon. However, to date, there is no scientific data on the presence of cattle egrets in landfill areas on a national scale. This study aimed to determine the abundance dynamics of cattle egrets at the Jatibarang landfill. Data collection on individual count dynamics was carried out using the Concentration Count method. Initially, this method involved identifying strategic areas to facilitate counting individual birds in each Active Zone. Bird censuses were conducted from 06:00 to 18:00 WIB using hourly photographic documentation. Data on the dynamics of cattle egret abundance in each Active Zone were tabulated using Microsoft Excel 2016, and graphs were produced to show the average number of individuals during the study. The results showed that the abundance dynamics varied among Active Zones, influenced by the status of waste disposal activities, which affected the availability of abundant food. The distribution patterns and utilization levels of cattle egrets in the three Active Zones differed due to variations in waste conditions, influencing the number and types of insects (larvae and adults). Active Zone 1 was intensively used by cattle egrets, with numbers reaching between 140 and 1505 individuals.